UAV and field survey investigation of a landslide triggered debris flow and dam formation in Eastern Carpathians - Mihu-Pintilie, Alin; Stoleriu, Cristian Constantin; Urzică, Andrei (Frontiers in Earth Science, 2024)
In the May-August period of 2010, major heavy rains impacted the Eastern Carpathians (Northeastern Romania), leading to flash floods and triggering numerous landslides. The extreme weather conditions caused damage to the road network, extensive forest destruction, and lead to formation of impounded lakes. One of the hardest-hit areas was the mountain tributaries catchments of the Bistrița watershed. Particularly, the most significant landslide-triggered debris flow event occurred in the upper Iapa valley (Neamț County). The landslide process started near the top of the Drumul Chinezilor ridge in the Goșmanu-Geamăna Massif (Tarcău Mountains), at an elevation of 875 m a.s.l., and the flow-slide fan obstructed a 300-meter section of the Iapa watercourse at 615 m a.s.l. This study compiles the climatic, anthropogenic, geological, and geomorphological evidence gathered during the field investigation in the October 2023 and utilizes Unmanned Aerial Vehicle (UAV) data collected to reconstruct the occurred debris flow-slide event. Additionally, it explores considerations regarding the reactivation of landslide processes, dam stability, and the future evolution of the impounded lake (Făgețel Lake). Furthermore, the lessons learned and future actions required to prevent further mass movement associated with debris flow-slide processes in prone areas of the Eastern Carpathians are discussed.